The Australasian TIME Consortium: Harnessing the combined potential of longitudinal population studies and administrative data to reduce preventable mortality in young people - O'Connor, Meredith; Kerr, Jessica; Kinner, Stuart; Heerde, Jessica; Downes, Marnie; Idrose, Sabrina; Borschmann, Rohan; Olsson, Craig (International Journal of Population Data Science, 2025)
Objective Preventable deaths (e.g., those resulting from self-harm, interpersonal violence, injury) among 11-39-year-olds are increasing in high-income countries. To date, limitations of available data have been a roadblock to building the evidence needed to inform preventive health and social policy responses. Administrative data usually lack comprehensive information on earlier life circumstances and experiences, while longitudinal population studies (LPS) have typically lacked the sample size needed for meaningful analysis of early deaths. We aim to overcome these data barriers by combining the strengths of administrative and LPS data, with the goal of informing multisectoral efforts targeting childhood and adolescent influences on preventable deaths between ages 11 and 39. Methods The International Mortality in Early adulthood (TIME) Consortium will harmonise data across eleven Australasian LPS involving >59,000 participants. Linkage to national death records will allow us to capture an estimated 1,100 deaths occurring from 11-39 years of age and ICD-10-AM coded causes. This presentation will discuss the value of combining the strengths of administrative and LPS data. It will also highlight the role of the Melbourne Children's LifeCourse Initiative (LifeCourse) in facilitating cross-cohort collaboration through data alignment and access pathways, as well as exploring models of engagement with policy and lived experience representatives. Results TIME’s design brings focus to multisectoral synergistic prevention opportunities earlier in the life course, prior to the peak period of preventable deaths. The data resource generated will be used to 1) estimate the effects of hypothetical interventions earlier in the life course on preventable mortality risk in the full population and for priority groups, and 2) quantify gains in life expectancy and economic productivity. Our knowledge co-creation processes, involving policy and lived experience advisors, facilitate influence on policy and service development. Conclusions The unique combination of rich early life data with sufficient statistical power will make TIME’s data resource distinctive internationally for its capacity to examine a comprehensive suite of child and adolescent influences on preventable mortality in the general population.